APOL1 renal risk variants are associated with obesity and body composition in African ancestry adults: An observational genotype–phenotype association study. Issue 45 (12th November 2021) - Nadkarni, Girish N.; Fei, Kezhen; Galarneau, Genevieve; Gao, Yan; Wilson, James G.; Cooper, Richard; Madden, Ebony B.; Denny, Joshua C.; Richardson, Lynne D.; Pollak, Martin; Loos, Ruth J. F.; Horowitz, Carol R.
Abstract : Abstract: While increased obesity prevalence among persons of African ancestry (AAs) compared to persons of European ancestry (EAs) is linked to social, environmental and behavioral factors, there are no gene variants that are common and significantly associated with obesity in AA populations. We sought to explore the association between ancestry specific renal risk variants in the apolipoprotein L1 ( APOL1 ) gene with obesity related traits in AAs. We conducted a genotype–phenotype association study from 3 electronic medical record linked cohorts (Bio Me Biobank, BioVU, nuGENE); randomized controlled trials (genetic testing to understand and address renal disease disparities) and prospective cohort study (Jackson Heart Study). We analyzed association of APOL1 renal risk variants with cross-sectional measures of obesity (average body mass index (BMI), and proportion of overweight and obesity) and with measures of body composition (in Jackson Heart Study). We had data on 11, 930 self-reported AA adults. Across cohorts, mean age was from 42 to 49 years and percentage female from 58% to 75.3%. Individuals who have 2 APOL1 risk alleles (14% of AAs) have 30% higher obesity odds compared to others (recessive model adjusted odds ratio 1.30; 95% confidence interval 1.16–1.41; P = 2.75 × 10 −6 ). An additive model better fit the association, in which each allele (47% of AAs) increases obesity odds by 1.13-fold (adjusted odds ratio 1.13; 95% confidence interval 1.07–1.19; P = 3.07 × 10 −6 ) and increases BMI by 0.36 kg/m 2 (∼1 kg, for 1.7 m height; P = 2 × 10 −4 ). APOL1 alleles are not associated with refined body composition traits overall but are significantly associated with fat free mass index in women [0.30 kg/m 2 increment per allele; P = .03]. Thus, renal risk variants in the APOL1 gene, found in nearly half of AAs, are associated with BMI and obesity in an additive manner. These variants could, either on their own or interacting with environmental factors, explain a proportion of ethnic disparities in obesity. Abstract : Supplemental Digital Content is available in the text